Pengaruh Corporate Governance terhadap Biaya Agensi pada Perusahaan Tekstil dan Garment yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014 – 2018 - Tri Wulandari (lppm.eka-prasetya.ac.id, 2020)
This study aims to determine the effect of managerial ownership on agency costs in textile companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. This is to determine the effect of institutional ownership on agency costs in textile companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. This research is quantitative research. The method used by the writer in analyzing the data in this research is descriptive statistical analysis. In this study, researchers used secondary data in the form of company records on financial reports related to this study. The results of this study are multiple linear regression equations showing each independent variable to the dependent variable. The value of α is -0.104, which indicates that agency costs decrease by -0.104 percent if managerial ownership (X1) and institutional ownership (X2) are equal to zero. The value of β1 is 0.346 which indicates that for every 1% increase in managerial ownership, agency costs will decrease by 0.346% assuming the other variables are constant. The value of β2 is 0.267 which indicates that for every 1% increase in institutional ownership, agency costs will decrease by 0.267%, assuming the other variables are constant.